Geographical equations of Swertia mussotii bioactivities: evidence from the western Sichuan region of China - Wang, Xiaobo; Shen, Cheng; Chen, Tao; Zhou, Xiaodan; Li, Yulin (Frontiers in Plant Science, 2023)
Swertia mussotii is the most authentic raw material used in Tibetan medicine in China for its various bioactivities. This natural medicine resource is at risk of being exhausted due to the double interference of climate change and anthropogenic over-collection. Little is known about habitat characteristics and the crucial environmental factors that influence the levels of active ingredients. The goal of this study is to understand the variability in the bioactive compound content of a wide range of wild S. mussotii as it adapts to changing environmental conditions. The target compound content of the whole plant material was analyzed with the environmental explanatory variables of the field sample sites using a constrained ordination method for their correlation analysis. The results show that 16.3 percent of the sampled wild S. mussotii populations with the highest bioactive content can be grouped into the elite type. The most prominent environmental variables affecting the content of major bioactive products include altitude, aspect, soil TK content, Fe content, and C/N and N/P ratios. Altitude and aspect put indirect effects that are mediated by plant height and density, N/P ratio puts a direct effect, while soil TK content, Fe content and C/N ratio have both direct and indirect effects on the bioactivity of S. mussotii. In addition to the total negative effects of altitude and C/N ratio, the remaining factors play a driving role. These findings demonstrate variation by geographical conditions across S. mussotii accessions for physiologic responses and secondary compounds in wild populations. The knowledge gained from this study can be used for environmental and plant physiology research, efficient collection of naturally active compounds, and conservation strategies for rare natural plant resources.